Die liturgie in die spieël van die Psalms - Vos, Casparus Johannes Adam (Verbum et ecclesia, 1998)
The liturgy as mirrored in the Psalms: The basic premise of this article is that meditation on the psalms leads us to look at them from a liturgical perspective. Since the liturgy is an expression of various acts and experiences offaith, the psalms - which are also an interpretation of acts of faith and lived faith - are a rich source of liturgical inspiration. This article illustrates the way the psalms provide the building material for various liturgical procedures. We shall be reading Psalm 24 very attentively with a view to sermon writing. This article is dedicated to the memory of the late Prof W S Prinsloo, an outstanding reader and exegete of the psalms.